Photocatalytic Degradation Of Phenol In Aqueous Solution Using Fe/Tio2 Thin Films Under Uv And Visible Light. - Mansor, Anis (2008)

(untitled)
Photocatalytic degradation of phenol by oxidation, utilizing doped TiO2 (Fe/TiO2) as photocatalyst in the form of immobilized thin films in a jacketed photocatalytic batch reactor was the subject of this research.